2012
DOI: 10.1038/cmi.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 90 inhibition by 17-DMAG lessens disease in the MRL/lpr mouse model of systemic lupus erythematosus

Abstract: Elevated expression of heat shock protein 90 (HSP90) has been found in kidneys and serum of systemic lupus erythematosus (SLE) patients and MRL/Mp-Fas lpr /Fas lpr (MRL/lpr) autoimmune mice. We investigated if inhibition of HSP90 would reduce disease in MRL/ lpr mice. In vitro, pretreatment of mesangial cells with HSP90 inhibitor Geldanamycin prior to immune-stimulation showed reduced expression of IL-6, IL-12 and NO. In vivo, we found HSP90 expression was elevated in MRL/lpr kidneys when compared to C57BL/6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 96 publications
(123 reference statements)
5
45
0
1
Order By: Relevance
“…In fact, DMAG-treated mice exhibited reduced macrophage and T-cell infiltration along with a decreased expression of proinflammatory genes (TNF-a, CCL2, and CCL5). Previous reports indicated that HSP90 inhibitors prevent inflammatory gene expression in different cell types, including cancer cells (36), leukocytes (17,37), and renal and vascular cells (15,17). In line with this, our studies in cultured mesangial and tubular cells mimicking hyperglycemic and inflammatory diabetic conditions demonstrated that DMAG inhibited the gene expression and protein secretion of CCL2 and also mitigated macrophage chemotaxis, further substantiating the in vivo findings.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In fact, DMAG-treated mice exhibited reduced macrophage and T-cell infiltration along with a decreased expression of proinflammatory genes (TNF-a, CCL2, and CCL5). Previous reports indicated that HSP90 inhibitors prevent inflammatory gene expression in different cell types, including cancer cells (36), leukocytes (17,37), and renal and vascular cells (15,17). In line with this, our studies in cultured mesangial and tubular cells mimicking hyperglycemic and inflammatory diabetic conditions demonstrated that DMAG inhibited the gene expression and protein secretion of CCL2 and also mitigated macrophage chemotaxis, further substantiating the in vivo findings.…”
Section: Discussionsupporting
confidence: 78%
“…Preclinical data implicate HSP90 as a promising anti-inflammatory target in rheumatoid arthritis, systemic lupus erythematosus, uveitis, liver injury, and cardiovascular disease models (12,(15)(16)(17)(18). In diabetic animals, HSP90 inhibition improved insulin sensitivity (19), high-fat diet-induced renal failure (20), and neurodegeneration (21), but the underlying mechanisms involved in these antidiabetic actions are not well defined.…”
mentioning
confidence: 99%
“…They bind to the ATP-binding domain of Hsp90 and disrupt its association with client proteins [20,21]. Recently, Shimp et al have shown that administration of 17-DMAG ameliorated SLE symptoms [22]. However, underlying mechanism has been unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological inhibition of Hsp90 function has therefore emerged as a promising method to ameliorate inflammatory cascades, as it has been demonstrated in various experimental mouse models of autoimmune diseases, including autoimmune encephalomyelitis (Dello Russo et al 2006), rheumatoid arthritis (Rice et al 2008;Yun et al 2011), and systemic lupus erythematosus (Han et al 2010;Shimp et al 2012a). Our own recent research work showed that, by downregulating T cell responses, this kind of treatment is also effective in mice with the experimentally induced subepidermal autoimmune blistering skin disease epidermolysis bullosa acquisita (Kasperkiewicz et al 2011).…”
Section: Introductionmentioning
confidence: 99%